2006
DOI: 10.1139/b06-112
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed banks and plant community assembly following disturbance by fire and logging in interior Douglas-fir forests of south-central British Columbia

Abstract: Relationships between soil seed banks and aboveground understory vegetation were examined in dry Douglas-fir (Pseudotsuga menziesii (Beissn.) Franco) forests near Kamloops, British Columbia, to compare the effects of different disturbance types (low and high severity fires and non-salvage logging), and to evaluate how seed banks contribute to post-disturbance vegetation establishment. Sites were selected to represent disturbances at 1, 5, and 10 years prior to sampling, and data were analyzed using nonparametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…In a companion paper (Stark et al 2006), we reported differences in the soil seed banks (seed density and species composition) of dry coniferous forests at 1, 5, and 10 years following different types and intensities of disturbance (undisturbed, low severity fire, high severity fire, and clear-cut logging). Here, we re-examine the seed bank data from mature forest and 1-yr post-logging and 1-yr post-fire disturbance types.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a companion paper (Stark et al 2006), we reported differences in the soil seed banks (seed density and species composition) of dry coniferous forests at 1, 5, and 10 years following different types and intensities of disturbance (undisturbed, low severity fire, high severity fire, and clear-cut logging). Here, we re-examine the seed bank data from mature forest and 1-yr post-logging and 1-yr post-fire disturbance types.…”
Section: Introductionmentioning
confidence: 96%
“…Seed limitation is most commonly observed in early stages of succession (Turnbull et al 2000), and can be manifested as an aggregated (under-dispersed) arrangement of seeds in the soil seed bank. As forests become more managed, there is increased need for baseline information not only on the role of the seed bank in post-disturbance plant community assembly (Stark et al 2006), but also on the extent to which seed bank species distribution patterns vary across the landscape. Pragmatically, this raises questions about the adequacy of current sampling approaches for capturing such variation and relating it to different scales of ecological inquiry (e.g., within-stand scales of \100 m versus between-stand scales of [10 km).…”
Section: Introductionmentioning
confidence: 99%
“…We examined shifts in the community structure of soil fungi using LH-PCR, and of nitrogen-fixing and denitrifying microbes using T-RFLP analysis of nifH and nosZ genes, respectively. latifolia) (Stark et al, 2006). Sites classified as 'high severity burns' had been exposed to a stand-destroying wildfire, with all needles on the trees consumed during the fire.…”
Section: Introductionmentioning
confidence: 99%
“…Neither distance to seed source nor any topographic variables could explain these differences as the influence of these bottom-up factors (i.e., slope, elevation, and distance to seed source) were consistent across disturbances. A decreased seed bank from repeated disturbances may be one explanation for the reduction in continued germination of Douglas-fir seedlings (Stark et al 2006. At the time of the wildfire these repeated disturbance stands were in the gray phase, thus we expect that these stands had similarly high seedling densities as we observed in gray phase stands.…”
Section: Tree Regeneration: Mixed Interactive Effects Of Fire and Barmentioning
confidence: 64%